Determination of Heavy Metal Ions and Organic Pollutants in Water Samples Using Ionic Liquids and Ionic Liquid-Modified Sorbents. (31st October 2019) - Tian, Minglei; Fang, Luwei; Yan, Xuemin; Xiao, Wei; Row, Kyung Ho
Abstract : Water pollution, especially by inorganic and organic substances, is considered as a critical problem worldwide. Several governmental agencies are listing an increasing number of compounds as serious problems in water because of their toxicity, bioaccumulation, and persistence. In recent decades, there has been considerable research on developing analytical methods of heavy metal ions and organic pollutants from water. Ionic liquids, as the environment-friendly solvents, have been applied in the analytical process owing to their unique physicochemical properties. This review summarizes the applications of ionic liquids in the determination of heavy metal ions and organic pollutants in water samples. In addition, some sorbents that were modified physically or chemically by ionic liquids were applied in the adsorption of pollutants. According to the results in all references, the application of new designed ionic liquids and related sorbents is expected to increase in the future